Decide Madrid: a case study on e-Participation - Pina, Vicente; Torres, Lourdes; Royo, Sonia; García-Rayado, Jaime (2019)
This paper analyses the award-winning e-participation initiative of th e city council of Madrid, Decide Madrid, to discover the critical succ ess factors at contextual, organizational and individual level. This a nalysis is carried out with desk research and semi-structured intervie ws. Results show that the most relevant success factors are the socio- economic context, the commitment of the city council, the method used to recruit the workers and the knowledge of senior managers about citi zen participation and ICTs. However, the lack of transparency and poor functioning of some of its participation activities are negatively af fecting its performance.